Men’s Positive and Negative Experiences Following Acute Myocardial Infarction - Solano-Ruiz, MCarmen (Int J Environ Res Public Health, 2021)
(1) Objective: To describe men’s experiences as acute myocardial infarction sufferers from a social phenomenological perspective, a year after the event (2) Methods: The phenomenological interview was used to capture the participants’ discourse. The data were analyzed according to the theoretical methodological approach of social phenomenology. (3) Results: The discourse analysis of the content produced the following categories, set out according reasons “why”: personal biography, knowledge set, warning signs prior to the illness, experience at the intensive care unit, and rehabilitation process; and reasons “for”: expectations as regards the illness, health professionals, and future social life and work prospects. (4) Conclusions: Participants had not established a healthy condition one year after myocardial infarction, perceiving a very thin line between life and death. Personal biography influences the coping of the disease. They feel like the illness helped them to create new meanings and value of life. They envisage a future full of great restrictions and uncertainty. The results of this study have underlined the need to involve care at all stages of the illness: the physical and emotional dependence upon admittance at the intensive care unit, the need to be cured, the constant demand for information about the illness, the difficulties encountered upon returning home, uncertainty about the future, etc. All these moments indicate that proper nursing care adapted to the specific needs of each individual and their family members must be provided in order to help them to overcome all the stages involved in this process. It is necessary to individualize care because the sense of reality is common and universal, but the ways of expressing are subjective, and it depended on the totality of experiences accumulated throughout life.